Efficient CTDSM based on GM-C quantiser and improved dynamic element matching - Sahu, Anil Kumar; Chandra, Vivek Kumar; Sinha, Ganesh Ram; Kumar Misra, Neeraj (IET circuits, devices & systems, 2020)
In this study, a continuous-time delta-sigma modulator (CTDSM) is developed using a Gm-C based noise-shaping quantiser (Gm-C-NSQ) with an improved dynamic element matching (i-DEM) algorithm. Here, a Gm-C integrator is used to develop NSQ, since it increases the effectiveness of the proposed modulator in terms of power consumption and die area. This Gm-C-NSQ uses only three dynamic latches to provide efficient quantisation level and to increase the order of noise shaping. Moreover, an i-DEM algorithm is utilised to reduce the non-linearities of the quantiser and mismatching error of the digital-to-analogue converters presented in the feedback structure of the modulator. Here, an 180 nm CMOS technology is used to design the proposed modulator and it functions at 2.6 MHz sampling frequency. Simulation results show that the proposed modulator can achieve a peak spurious-free dynamic range (SFDR) of 93.67 dB and a peak signal-to-noise ratio of 87.38 dB for 20 kHz signal bandwidth. Furthermore, the proposed modulator consumes 0.0863 mW power when 1.2 V supply voltage is applied.